Tenofovir or Zidovudine in Second-Line Antiretroviral Therapy after Stavudine Failure in Southern Africa. Issue 5 (July 2014) - Wandeler, Gilles; Gerber, Florian; Rohr, Julia; Chi, Benjamin H; Orrell, Catherine; Chimbetete, Cleophas; Prozesky, Hans; Boulle, Andrew; Hoffmann, Christopher J; Gsponer, Thomas; Fox, Matthew P; Zwahlen, Marcel; et al.
Background: There is debate over using tenofovir or zidovudine alongside lamivudine in second-line anti-retroviral therapy (ART) following stavudine failure. We analysed outcomes in cohorts from South Africa, Zambia and Zimbabwe Methods: Patients aged ≥16 years who switched from a first-line regimen including stavudine to a ritonavir-boosted lopinavir-based second-line regimen with lamivudine or emtricitabine and zidovudine or tenofovir in seven ART programmes in southern Africa were included. We estimated the causal effect of receiving tenofovir or zidovudine on mortality and virological failure using Cox proportional hazards marginal structural models. Its parameters were estimated using inverse probability of treatment weights. Baseline characteristics were age, sex, calendar year and country. CD4 + T-cell count, creatinine and haemoglobin levels were included as time-dependent confounders. Results: A total of 1, 256 patients on second-line ART, including 958 on tenofovir, were analysed. Patients on tenofovir were more likely to have switched to second-line ART in recent years, spent more time on first-line ART (33 versus 24 months) and had lower CD4 + T-cell counts (172 versus 341 cells/ml) at initiation of second-line ART. The adjusted hazard ratio comparing tenofovir with zidovudine was 1.00 (95% CI 0.59, 1.68) for virological failure and 1.40 (0.57, 3.41) for death. Conclusions: We did not find any difference in treatment outcomes between patients on tenofovir or zidovudine; however, the precision of our estimates was limited. There is an urgent need for randomized trials to inform second-line ART strategies in resource-limited settings.